Correction to: Individual-and community-level determinants of neonatal mortality in the emerging regions of Ethiopia: a multilevel mixed-effect analysis - Getayeneh Antehunegn Tesema; Misganaw Gebrie Worku (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article.